Students Perception of Teacher Talk in English Teaching Learning Process (A Survey Research of Fifth Semesters at English Education Study Program during Covid-19 Pandemic) - Andi Astri Awwaliyah; Nurdin Noni; Amirullah Abduh (Journal of Excellence in English Language Education, 2022)
The purpose of this study was to determine students’ perception of teacher talk in English teaching learning process in the fifth semester at English education study program during the COVID-19 pandemic. This research is quantitative research, using survey research. The population in this study were 172 students from class A, B, C, D, and class Pare-Pare who used voluntary sampling. Data collection techniques through the distribution of questionnaires. Data were analyzed by descriptive analysis. The results showed that student’s perception of teacher talk in the teaching and learning process of Fifth Semesters at English Education Study Program during COVID-19 Pandemic was in positive classification. The conclusion, students were enthusiastic with the Teacher Talk that applied by the teacher in English Teaching learning Process.